2016
DOI: 10.1039/c6cp00242k
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation behavior of shear-induced crystallization precursors in isotactic polypropylene containing sorbitol-based nucleating agents with different nucleating abilities

Abstract: The nature of shear-induced crystallization precursors, especially their relaxation behaviour, is an important issue in polymer chemical physics. In our work, relaxation behavior of shear-induced crystallization precursors in isotactic polypropylene containing various sorbitol-based nucleating agents (NAs) with different nucleating abilities was investigated by using both rheological and in situ small angle X-ray scattering (SAXS) methods. Rheological crystallization kinetics results showed that the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…For both pure iPP and nucleated iPP, the sheared samples present the fastest crystallization rates, while the quiescent samples present the slowest crystallization rates. The relaxation treatment at 170°C obviously decelerates the crystallization rates of either iPP or β-nucleated iPP compared with samples that have not been relaxed, and longer relaxation time makes the crystallization rates of relaxed samples closer to the quiescent samples, which is in 2 International Journal of Polymer Science agreement with previous studies that also found that relaxation caused attenuation of shear-enhanced crystallization because of the dissolution of shear-induced nucleation precursors [17,18]. The relaxation temperature was set close to the processing temperature in realistic production which was lower than the equilibrium melting point of iPP to mimic thermal treatment in real processing.…”
Section: Thermal Stability and Lifetime Of Shear-inducedsupporting
confidence: 87%
See 2 more Smart Citations
“…For both pure iPP and nucleated iPP, the sheared samples present the fastest crystallization rates, while the quiescent samples present the slowest crystallization rates. The relaxation treatment at 170°C obviously decelerates the crystallization rates of either iPP or β-nucleated iPP compared with samples that have not been relaxed, and longer relaxation time makes the crystallization rates of relaxed samples closer to the quiescent samples, which is in 2 International Journal of Polymer Science agreement with previous studies that also found that relaxation caused attenuation of shear-enhanced crystallization because of the dissolution of shear-induced nucleation precursors [17,18]. The relaxation temperature was set close to the processing temperature in realistic production which was lower than the equilibrium melting point of iPP to mimic thermal treatment in real processing.…”
Section: Thermal Stability and Lifetime Of Shear-inducedsupporting
confidence: 87%
“…This result is close to the value of the iPP precursor (ca. 200 kJ/mol) proposed by Janeschitz-Kriegl [24], 210 kJ/mol calculated by Cavallo et al [17], and 160 kJ/mol calculated by Fan et al [18] and is much larger than the energy of activation for viscous flow (∼44 kJ/mol for iPP) [25] suggesting that the detachment of polymer chain segments from the oriented nuclei is the limiting step in the process of shear-induced precursor relaxation not diffusion of the detached stem into the melt.…”
Section: Activation Energies Of Shear-induced Precursors In β-mentioning
confidence: 77%
See 1 more Smart Citation
“…For a representative semi‐crystalline polymer, isotactic polypropylene (iPP), the use of NAs is of special significance because of its relatively slow crystallization rate. By introducing various NAs, not only the crystallization kinetic could be accelerated, which shortens the processing cycle time, but also the physical properties of iPP including stiffness, toughness, and transparency have been remarkably improved. Among diverse NAs for iPP, β‐NA is one of the most extensively studied and widely used NAs .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, nucleation is the slow and limiting step and thus requires a higher degree of supercooling . Of the considerable efforts made to accelerate the nucleation of iPP and promote the crystallization of iPP in previous studies, dispersing nucleating agents (NAs) into the polymer matrix during melt processing is one of the most efficient and precedented . NA reduces the free energy barrier of nucleation by providing a suitable surface for the polymer to adhere to and grow into desired morphologies, such as that of spherulites.…”
Section: Introductionmentioning
confidence: 99%